Relationships between individual attributes, emotional exhaustion and counter productive work behavior among public sector employees in Malaysia - Raman, Ponniah (2013)
The Malaysian Government has recognized Human Capital Development (HCD) as a vital thrust for public sector innovation in this dynamic working world led by advanced globalization. The Public Sector in Malaysia is constantly looking forward to renew and improve public services and the quality of workforce with many plans, programs and strategies. To fulfill this aspiration, it is important to gain an understanding of the frontline staffs in public sector because they have extensive interaction with public and create the first impression towards Government efforts. The main objective of this research is to study the effect of personality, emotional intelligence,affectivity, emotional labor and emotional exhaustion on counterproductive work behaviour of frontline staffs in the public sector. Up to now the literature shows that very little academic research had been carried out in this area among frontline staff especially in Malaysian Public Sector. A survey (self-rated by the respondents) with established constructs was carried out to 625 frontline staffs working in 25 ministries in Malaysia. The data analysis was carried out using IBM-SPSS/PC V20.0 for descriptive and inferential statistics. The descriptive analysis shows the profile of respondents and perceptions of the variables. Whereas, the inferential statistics (Hierarchical Regression) was used to compute difference of mean, relationship and the mediation effect of emotional labor. The findings of this study provided a better understanding of the predictors of emotional labor and subsequently its impact to the emotional exhaustion and counterproductive work behavior among the frontline staff. Besides that, through the integrated model the study identified the mediating roles (partial mediator) of emotional labor between emotional intelligence and emotional exhaustion and also between personality and counterproductive work behavior. This exploratory study provides theoretical basis, empirical evidence and a data-base to develop new strategies, further research and review of the policy involving frontline staffs in public sector to have right skills and appropriate training to manage their emotion.